24. PREIMPLANTATION GENETIC TESTING FOR ANEUPLOIDIES WITH NGS ON MINISEQ. A RELIABLE ALTERNATIVE FOR SMALL LABORATORIES. (August 2019) - Papaevripidou, I.; Alexandrou, A.; Constantinou, E.; Theodosiou, A.; Evangelidou, P.; Sismani, C.
Abstract : Introduction: The demand for Preimplantation Genetic Testing for aneuploidy (PGT-A) used in IVF, is constantly increasing to improve pregnancy outcomes by transferring euploid embryos. The introduction of NGS has led to rapid transition of PGT-A from array platforms to low depth high-throughput whole genome sequencing which is now implemented in many laboratories worldwide. However, for small laboratories, the transition from array platforms to NGS should also take into consideration cost effectiveness. The aim of this study was to achieve the transition from array-CGH to NGS using the VeriSeq TM PGS (Illumina Inc.), on the MiniSeq, which is the existing platform of the Department. Consequently, the current study compares PGT-A results between array-CGH and NGS and also directly compares NGS results from MiniSeq and MiSeq, the platform for which VeriSeq TM PGS is already validated. Materials and Methods: In total 110 amplified biopsy samples were included and blindly analyzed in this study which was divided into three phases. The first included 30 biopsies of day-3(13) and day-5(17) embryos that were previously analyzed using array-CGH. These samples were sequenced on both MiSeqDx and MiniSeq platforms (Illumina Inc.). For the second phase, 80 amplified biopsy samples (day-5), with segmental, mosaic or full aneuploidies were run on the MiniSeq platform with paired-end (2 × 36) sequencing using the MiniSeq High Output Reagent Kit (75-cycles) (Illumina Inc.). The last phase was to detect the sensitivity for mosaicism by mixing serial diluted samples with different chromosomal losses/gains to give 50%, 40%, 30% and 20% aneuploidy. Library preparations on all phases were carried out using VeriSeq TM PGS (Illumina Inc.) following manufacturer's recommendations. For the MiniSeq, the secondary analysis of alignment was performed on-instrument with BWA-MEM to produce aligned reads. An in-house pipeline was implemented to adjust the headers within bam files in order to facilitate the downstream analysis of samples on Bluefuse Multi v4.4. Results: Comparative results on both platforms MiniSeq and MiSeq demonstrated 100% concordance, placing our in house pipeline using MiniSeq platform as a cost effective alternative approach for PGT-A, especially for small laboratories. The two different techniques array-CGH and NGS showed concordant results in 105/107 (98%) of the samples tested and overall concordance rate of 99.8% (2410/2415) per analyzed chromosome. All differences detected were attributed to mosaicism. Three day-3 embryos were excluded from the analysis as they failed to pass the VeriSeq TM PGS quality criteria. NGS successfully detected all segmental, mosaic or full aneuploidies (smallest 15Mb) depicting superior profiles than array-CGH due to the broader dynamic range. The sensitivity of the NGS platform for mosaicism detection was defined to be 20%. Conclusion: Our validation study result demonstrates that VeriSeq is fully compatible with the MiniSeq platform and in full concordance with results obtained from the MiSeq. The results showed that PGT-A with NGS can identify more precisely chromosomal mosaicism and segmental aneuploidy than the aCGH platform. With the cost of sequencing gradually decreasing, the cost of PGT-A will make the service accessible to all fertility patients in order to enhance their chances of successful pregnancy.